The gatekeepers of contact: child-caregiver dyads and parental prison visitation - Tasca, Melinda (Criminal justice and behavior, 2016)
As gatekeepers, caregivers play a pivotal role in the facilitation of parental prison contact, and some caregivers may be more likely to take children to visit than others. To advance prior work, I used data collected from structured interviews with prisoners in Arizona to test two hypotheses. Specifically, I expected that children with grandmothers (n = 684) and children with mothers (n = 300) would be more likely to visit mothers and fathers in prison relative to other child?caregiver dyads. Logistic regression analyses confirmed these hypotheses in both maternal and paternal models, independent of controls. Child situational factors, prisoner characteristics, stressors, and institutional barriers also predicted visits; although effects differed depending upon which parent was in prison. By providing insight into the maintenance of family ties during confinement, this study informs research and policy with respect to prison contact and reentry.